Exogenous IBA stimulatory effects on root formation of Actinidia deliciosa rootstock and Actinidia arguta male scion stem cuttings - Sekhukhune, Mapogo Kgetjepe; Maila, Mmatshelo Yvonne (Frontiers in Sustainable Food Systems, 2024)
Propagation of kiwifruit plants (Actinidia spp.) had been mostly done by seeds. Vegetative propagation using hardwood-stem cuttings (SCs) tend to be recalcitrant to rooting, without the use of plant growth regulators (PGRs). However, vegetative propagation offers several advantages over sexual propagation, among them being crop homogeneity of the technique. A study was conducted to investigate the responses of kiwifruit SCs from Actinidia deliciosa rootstock and Actinidia arguta male scion SCs treated with indole-3-butyric acid (IBA) concentrations at low (10, 100 ppm), medium (1000, 10 000 ppm) and high (100 000 ppm) levels. Parallel experiments for A. deliciosa and A. arguta's treatments were arranged in a randomised complete block design, with 12 replications. In A. deliciosa, treatments had significant (P≤0.05) effects in rooting percentage, number of roots, root length, size of callus formation and callus percentage, except for dry root mass. In A. arguta, treatments also, showed significant (P≤0.05) effects in the number of roots, root length and dry root mass, except for the rooting percentage. No callus formation was observed in A. arguta. Relative to the control, in A. deliciosa, the highest (42%) rooting percentage and lengthy (0.3 cm) roots, both were observed at the medium (10 000 ppm) IBA concentration, whereas the most (0.29) number of roots were produced at the highest (100 000 ppm) IBA concentration. Calli percentage (94%) was highest at low (100 ppm) IBA, while the size of callus formation was biggest (2.8) at the highest IBA concentration of 100 000 ppm, when compared to the control. In A. arguta, the greatest number of roots (1.08) and root mass (0.07g) were attained at the medium IBA concentration of 10 000 ppm. The longest (0.94 cm) root length was achieved at the low IBA concentration of 100 ppm. Actinidia arguta male required low to medium (100 to 10 000 ppm) concentrations of IBA for proper roots stimulation and development, whereas in A. deliciosa, highest rooting percentage paired with callus formation, was achieved at medium to higher IBA concentrations (10 000 to 100 000 ppm). In conclusion, A. arguta showed good rooting responses, when compared to A. deliciosa.